Cyber Attacks Undermine Audit Accuracy and Data Security in Banking: Serangan Siber Merusak Akurasi Audit dan Keamanan Data di Perbankan - Arkad, Omar Mohammed; Kazim, Adel Muwaffaq; Hadi, Omar Ali (Academia Open, 2025)
General Background: The rise of digital financial systems has increased banking institutions' exposure to cyber threats, particularly security system breaches, posing risks to data integrity and audit operations. Specific Background: Iraqi commercial banks have experienced frequent cyber attacks on accounting information systems, raising concerns about audit accuracy, data manipulation, and access delays. However, research on these threats' direct consequences for auditing remains scarce. Knowledge Gap: Prior studies emphasize cybersecurity measures but overlook how cyber attacks disrupt audit processes, transparency, and efficiency. Aims: This study evaluates security breaches' effects on auditing, assesses data manipulation risks, examines delays in financial access, and explores cyber incident investigations' role in mitigating threats. Results: Findings reveal that hacking compromises audit accuracy, causes operational delays, and threatens financial security, emphasizing the need for advanced cybersecurity measures. Novelty: This study bridges cybersecurity and auditing, providing empirical evidence on cyber threats’ disruption of audit performance. Implications: Strengthening cybersecurity frameworks is essential for maintaining audit reliability and financial sector stability. Highlights: Cyber attacks compromise audit efficiency, data integrity, and financial security. Hacking, data manipulation, and delays weaken audit accuracy and transparency. Strengthening cybersecurity enhances audit reliability and banking sector stability. Keywords: Cybersecurity, Audit, Cyberattacks, Accounting Information Systems